Research without prior consent in paediatric emergency and critical care medicine. Issue 2 (February 2020) - Picton, Aled; Woolfall, Kerry; Lyttle, Mark D.; Hartshorn, Stuart
Abstract: Children and young peoples' healthcare should be evidence-based yet many treatments are unlicensed or prescribed off-label. Research is needed, but prospective informed consent for many emergency and critical care trials is neither feasible nor ethical – treatments are time critical, and delays for research discussions may cause harm. Research without prior consent (RWPC) is a practical approach which facilitates such research. Trial interventions are administered immediately to eligible patients, and consent for ongoing study involvement is sought after the emergency situation has passed. This has been permitted in the United Kingdom since an amendment to legislation in 2008, and subsequently employed by several trials. Studies demonstrate that most parents are supportive of this approach provided their child's safety is not compromised, and research discussions are appropriately timed. Practitioners with no experience of RWPC often initially report anxiety about taking this approach, but study experience and training helps change perspectives. Sadly, some children enrolled into such studies will die. Approaching bereaved families for consent requires a bespoke approach, conducted with care and sensitivity. Future research should explore the acceptability of higher risk trials, the viewpoints of children with first-hand experience of this method, and international perspectives.